2021
DOI: 10.3390/ijms22105132
|View full text |Cite
|
Sign up to set email alerts
|

When the Blood Hits Your Brain: The Neurotoxicity of Extravasated Blood

Abstract: Hemorrhage in the central nervous system (CNS), including intracerebral hemorrhage (ICH), intraventricular hemorrhage (IVH), and aneurysmal subarachnoid hemorrhage (aSAH), remains highly morbid. Trials of medical management for these conditions over recent decades have been largely unsuccessful in improving outcome and reducing mortality. Beyond its role in creating mass effect, the presence of extravasated blood in patients with CNS hemorrhage is generally overlooked. Since trials of surgical intervention to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 234 publications
(246 reference statements)
0
16
0
Order By: Relevance
“…The mechanisms responsible for brain damage within a cerebral hematoma are numerous and complex: initially, there is a direct effect of acute bleeding into the brain parenchyma, causing a mass effect, which is subsequently accompanied by hemorrhage arrest in about two-thirds of patients. However, in the remaining third of patients, the hematoma continues to grow during the first 24 hours, which contributes to an additional mass effect, midline shift and leads to further neurological deficit and an increased risk of adverse outcomes [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible for brain damage within a cerebral hematoma are numerous and complex: initially, there is a direct effect of acute bleeding into the brain parenchyma, causing a mass effect, which is subsequently accompanied by hemorrhage arrest in about two-thirds of patients. However, in the remaining third of patients, the hematoma continues to grow during the first 24 hours, which contributes to an additional mass effect, midline shift and leads to further neurological deficit and an increased risk of adverse outcomes [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Oxyhemoglobin and its metabolites are considered to be the main sources of reactive oxygen species (ROS) in the pathophysiological process of SAH (Hugelshofer et al, 2018). After hemolysis, tetrameric hemoglobin is released from RBCs and degrades gradually, producing toxic intermediates (Stokum et al, 2021). Among them, heme is considered more toxic than hemoglobin (Bulters et al, 2018).…”
Section: Hemoglobin As a Source Of Peroxidementioning
confidence: 99%
“…However, the neuroinflammatory cascade triggered by the immune response after ICH further aggravates neurological damage. It has been demonstrated that pathophysiological changes in the NVU and glial network after ICH provide therapeutic targets for ameliorating ICH-induced secondary brain injury (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%